Librarians’ Perceived Ease-Of-Use And Usefulness Of Cloud Computing For University Library Services In Kwara State, Nigeria - Abdullahi Olayinka Isiaka; Abdulmunin Isah (Department Library of Governance Institut of Home Affairs, 2025)
Abstract Problem Statement: The university libraries' scenery has developed significantly over the past few decades, driven by rapid technological advancements and the increasing demand for digital resources. The use and integration of cloud computing in university libraries has effectively impacted and improved service delivery positively. In Kwara State, Nigeria, university libraries face infrastructure challenges amid rising digital demands, making cloud computing adoption critical for service enhancement. Purpose: The study explored the librarians' perceived ease-of-use and usefulness of cloud computing for university library services in Kwara State, Nigeria. Method: .The study utilizes a survey design approach; data were collected through a questionnaire from a sample of 116 librarians and library officers from all nine university libraries in Kwara State. The questionnaire was validated by 2 professionals in the field of Library and Information Science. The data collected were analyzed with the use of IBM SPSS v26 and presented with frequency tables and simple percentages. Result: The findings revealed the librarians' perceived ease-of-use of cloud computing for university library services, such as: it simplifies workflows; no errors when using it; it makes work faster and much easier; it is easy to get cloud computing to do what you want it to do; and its interface is friendly and easy to navigate. The findings further revealed the librarians' perceived usefulness of cloud computing for university library services, such as: it makes work more efficient and effective; it increases professional productivity; it helps in information dissemination and transfer of operation; and services of the library to the cloud will reduce costs. The findings also identified several perceived challenges of cloud computing for university library services, such as slow/poor internet connections, adaptability and dependency on outsiders, and data security and privacy problems, among others. Conclusion: The study concluded that cloud computing offers significant advantages, such as improved access to resources, cost savings, and enhanced collaboration in university libraries. Recommendations from the study include that the university libraries should try to tap and maintain the merits and benefits attached to the use of cloud computing to better provide effective services. This study contributes to the benefits of cloud computing adoption, usage, and integration into university library services, ultimately enhancing the role of librarians in information delivery and supporting academic excellence.